Maternal and perinatal outcomes of prolonged second stage of labour: a historical cohort study of over 51,000 women - Catriona Young; Sohinee Bhattacharya; Andrea Woolner; Amy Ingram; Nicole Smith; Edwin-Amalraj Raja; Mairead Black (BMC, 2023)
Background Prolonged second stage of labour has been associated with adverse maternal and perinatal outcomes. The maximum length of the second stage from full dilatation to birth of the baby remains controversial. Our aim was to determine whether extending second stage of labour was associated with adverse maternal and perinatal outcomes. Methods A retrospective cohort study was conducted using routinely collected hospital data from 51592 births in Aberdeen Maternity Hospital between 2000 and 2016. The hospital followed the local guidance of allowing second stage of labour to extend by an hour compared to national guidelines since 2008 (nulliparous and parous). The increasing duration of second stage of labour was the exposure. Baseline characteristics, maternal and perinatal outcomes were compared between women who had a second stage labour of (a) ≤ 3 h and (b) > 3 h duration for nulliparous women; and (a) ≤ 2 h or (b) > 2 h for parous women. An additional model was run that treated the duration of second stage of labour as a continuous variable (measured in hours). All the adjusted models accounted for: age, BMI, smoking status, deprivation category, induced birth, epidural, oxytocin, gestational age, baby birthweight, mode of birth and parity (only for the final model). Results Each hourly increase in the second stage of labour was associated with an increased risk of obstetric anal sphincter injury (aOR 1.21 95% CI 1.16,1.25), having an episiotomy (aOR 1.48 95% CI 1.45, 1.52) and postpartum haemorrhage (aOR 1.27 95% CI 1.25, 1.30). The rates of caesarean and forceps delivery also increased when second stage duration increased (aOR 2.60 95% CI 2.50, 2.70, and aOR 2.44 95% CI 2.38, 2.51, respectively.) Overall adverse perinatal outcomes were not found to change significantly with duration of second stage on multivariate analysis. Conclusions As the duration of second stage of labour increased each hour, the risk of obstetric anal sphincter injuries, episiotomies and PPH increases significantly. Women were over 2 times more likely to have a forceps or caesarean birth. The association between adverse perinatal outcomes and the duration of second stage of labour was less convincing in this study.